2011
DOI: 10.2146/ajhp100133
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for fondaparinux in perioperative bridging?

Abstract: The role of fondaparinux in perioperative bridge therapy has not been established, and there are some important limitations to its use as a routine bridging agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Results obtained for fondaparinux showed that whatever the used methodology (current and improved), the presence of fondaparinux could impact the tests, except for the higher dilution (ie, Biophen ® DiXaI ® [1:50]) (Figure . Although a switching between fondaparinux and betrixaban is unlikely, the increase in the concentration of the buffer could be one possibility to avoid this interference. However, we have to keep in mind that even if some chromogenic anti‐Xa assays are specific for direct factor Xa inhibitors, none of these are able to discriminate between direct factor Xa inhibitors which may be a problem when no information on the drug taken by the patients is available…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained for fondaparinux showed that whatever the used methodology (current and improved), the presence of fondaparinux could impact the tests, except for the higher dilution (ie, Biophen ® DiXaI ® [1:50]) (Figure . Although a switching between fondaparinux and betrixaban is unlikely, the increase in the concentration of the buffer could be one possibility to avoid this interference. However, we have to keep in mind that even if some chromogenic anti‐Xa assays are specific for direct factor Xa inhibitors, none of these are able to discriminate between direct factor Xa inhibitors which may be a problem when no information on the drug taken by the patients is available…”
Section: Discussionmentioning
confidence: 99%
“…Initial recommendations for discontinuation of fondaparinux preoperatively would be 3-5 halflives, similar to other anticoagulants. This recommendation is based solely on expert opinion, with no differentiation between the 2.5 mg prophylaxis dose and 5-10 mg therapeutic dose [122]. In patients with good renal function, this would be at least 2 days prior to a surgical procedure with minimal bleeding risk and 4 days prior to a surgical procedure with a high risk of bleeding.…”
Section: Fondaparinux (Arixtra)mentioning
confidence: 99%
“…Fondaparinux inhibits thrombin formation indirectly by selectively binding to antithrombin III, thus neutralizing factor Xa. 74 Rivaroxaban and apixaban act via direct inhibition and bind directly to the active binding site of factor Xa blocking the interaction with substrates. 75 No clinical trials have evaluated the length of time required for preoperative discontinuation; however, based on time of elimination from the body, they should be stopped at least 2 days preoperatively for patients without a high risk of bleeding and 4 days preoperatively in patients with a high risk of bleeding.…”
Section: Factor Xa Inhibitorsmentioning
confidence: 99%
“…These should be stopped at least 12 to 24 hours preoperatively. 74,79 Unlike its efficacy with UFH, protamine does not completely eradicate the anti-Xa activity of low-molecular-weight heparin. However, for patients who experience bleeding while receiving low-molecular-weight heparin, protamine sulfate (1 mg/100 anti-Xa units of low-molecular-weight heparin) may reduce clinical bleeding.…”
Section: Heparinmentioning
confidence: 99%